The legal position of the Dalmatian merchants in medieval Lübeck - Jiří Bílý (Journal on European History of Law)
This study examines the social standing and influence of Dalmatian merchants in the Hanseatic town of Lübeck during the Late Middle Ages (1350-1510). Contrary to traditional beliefs, the research uncovers evidence suggesting that the Dalmatian merchants enjoyed greater social prestige, active political participation, and strong financial standing. Drawing from diverse sources, including narratives, guild membership records, and market activities, the study challenges the notion of the Dalmatian merchants as a marginalized group and explores their fluctuating social status over time.